2013
DOI: 10.2478/cpe-2013-0033
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Supercritical Fluid Extraction in Membrane Cleaning Process by Addition of Organic Solvents

Abstract: In this study, the process of membrane cleaning by supercritical fluid extraction was investigated. Polypropylene microfiltration membranes, contaminated with oils, were treated in a batch process with a supercritical fluid (SCF). As extractant, pure supercritical carbon dioxide or supercritical carbon dioxide with admixtures of methanol, ethanol and isopropanol were used. Single-stage and multi-stage extraction was carried out and process efficiency was determined. The obtained results showed that addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…The first results on membrane cleaning utilising supercritical CO 2 performed in a batch reactor, at T = 40 • C, 70 • C and 100 • C and p = 18 MPa [11] seemed to be promising. However, research demonstrated drawbacks such us execution of the process in a batch system not suitable for scaling up.…”
Section: Introductionmentioning
confidence: 93%
“…The first results on membrane cleaning utilising supercritical CO 2 performed in a batch reactor, at T = 40 • C, 70 • C and 100 • C and p = 18 MPa [11] seemed to be promising. However, research demonstrated drawbacks such us execution of the process in a batch system not suitable for scaling up.…”
Section: Introductionmentioning
confidence: 93%
“…Distillation under pressure is always preferred for the recovery and recycling of ILs, because of its low vapor pressure. However, non-volatile and thermal-sensitive solutes are separated by other methods including, extraction with organic solvents or supercritical carbon dioxide and membrane separation processes [116].…”
Section: The Recovery and Reuse Of Ilsmentioning
confidence: 99%
“…The specific case of cleaning polypropylene microfiltration membranes, contaminated with a model contaminant (soybean oil), using pure scCO 2 or scCO 2 with minor amounts of organic solvents, was studied extensively. It was shown that the addition of minor amounts of organic solvents to scCO 2 enhanced the process rate (Krzysztoforski et al, 2013;Michałek et al, 2015). Moreover, it was proven that scCO 2 does not deteriorate the material properties of the polypropylene microfiltration membrane (Tarabasz et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…The rate of the cleaning process depends on numerous parameters, such as the morphology of the porous material, the physical properties of the supercritical fluid, process conditions, the type of the contaminant and thermodynamic equilibria (limited or full miscibility of contaminant and solvent), the geometry and the hydrodynamics of the cleaning vessel, and -for liquid contaminants -possible capillary effects, as for low values of the capillary number Ca (the force ratio of drag/surface tension), flow through porous media is controlled by capillary forces. Examples of cleaning processes for porous materials, involving SCFs as cleaning media, include, among others, purification of cork stopper (Taylor et al, 2000), drying of alcogels (Özbakır and Erkey, 2015), soil remediation (Cocero et al, 2000), and cleaning of microfiltration membranes (Krzysztoforski et al, 2013;Michałek et al, 2015).…”
Section: Introductionmentioning
confidence: 99%